Volatile compounds from leaves of Aegle marmelos (L.) Correa grown in Cuba - Jorge A. Pino (Revista CENIC. Ciencias Químicas, 2005)
Aegle marmelos (L.) Correa which belongs to the Rutaceae family is abundantly available all over India. Almost every part of the plant is used in traditional medicine of this region. Volatile compounds from leaves of plants grown in Cuba were isolated by the standard method of hydrodistillation as an oil which yielded 0.31 % (v/m). Analysis of the leaf oil by capillary gas chromatography and gas chromatography-mass spectrometry resulted in the identification of 65 components comprising more than 85 % of the total oil. The leaf oil was constituted mainly of sesquiterpene compounds, whereas Indian oil was rich in monoterpene compounds. Major components were b-caryophyllene (10.0 %) and d- cadinene (12.1 %).